Perioperative airway management techniques and complications in patients with temporomandibular joint ankylosis: Experience from a tertiary care teaching institute - Anjan Trikha; Ajoy Roychoudhury; Devalina Goswami; Souvik Maitra; Ongkila Bhutia; Dalim Kumar Baidya (Saudi Journal of Anaesthesia)
Background and Aims: Temporomandibular Joint (TMJ) ankylosis patients pose serious anesthetic challenges due to difficult airway and obstructive sleep apnoea (OSA). However, data are sparse on anesthetic management and perioperative outcomes of such patients. This study aimed to identify the anesthetic and airway management techniques in children and adolescents with TMJ ankylosis and whether the presence of retrognathia and OSA increases the risk of airway-related complications. Materials and Methods: A retrospective anesthetic chart review of TMJ ankylosis patients undergoing maxillo-facial surgery from 2008 to 2018 in a tertiary care teaching hospital in India was performed. Available anesthetic data were tabulated and analyzed. Difficult mask ventilation, use of nasopharyngeal airway (NPA), difficult intubation, desaturation at induction and extubation, maneuvers to open the airway at extubation, and any post-operative anesthetic complications were noted. Results: Three hundred seventy-two children including 85 patients of OSA were available for analysis. All patients with OSA had retrognathia. Fiber-optic bronchoscopy (FOB) guided intubation was performed in 362 (97.3%) patients. Desflurane and fentanyl were common anesthetics used for the maintenance of anesthesia. Difficult mask ventilation, use of nasopharyngeal airway (NPA) and requirement of airway maneuvers were more common in OSA patients than in non-OSA patients. Difficult mask ventilation was observed in 18.0% and difficult intubation in 12.9% of patients. Desaturation at induction was noted in 5.1% of patients but none required emergency surgical airway access. Maneuvres to open the airway at extubation were required in 24.5% of patients and the incidence of desaturation at extubation was 7.2%. However, no serious adverse event was noted and only one patient required reintubation. Conclusion: FOB-guided intubation should be considered the technique of choice in TMJ ankylosis patients. In the presence of retrognathia and OSA chance of difficult mask ventilation, requirement of NPA and difficulty in maintaining the airway after extubation increase significantly.